Cross-Talk in Viral Defense Signaling in Plants - Moon, Ju Y.; Park, Jeong M. (Frontiers in Microbiology, 2016)
Viruses are obligate intracellular parasites that have small genomes with limited coding capacity; therefore, they extensively use host intracellular machinery for their replication and infection in host cells. In recent years, it was elucidated that plants have evolved intricate defense mechanisms to prevent or limit damage from such pathogens. Plants employ two major strategies to counteract virus infections: resistance (R) gene-mediated and RNA silencing-based defenses. In this review, plant defenses and viral counter defenses are described, as are recent studies examining the cross-talk between different plant defense mechanisms.